EDUKASI KERAJINAN DAUN KELAPA UNTUK PENGEMBANGAN INDUSTRI KREATIF DESA DURIAN LOMBOK TENGAH - Alda Fadila; Aurelius RL Teluma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2019)
The partner of the EDKERDAPA group activity is the residents of Durian village, Janapria sub-district, Central Lombok district, West Nusa Tenggara Province (NTB). Durian Village is a village with an area of around 476 ha which has extensive coconut plantations. The group identified several community problems, namely: 1) Lack of understanding of creative industries and handicrafts both in the production and marketing stages; 2) The lack of willingness and enthusiasm of Durian villagers to make a new innovation, most married women in Durian village do not work and only become housewives; 3) The lack of knowledge about online marketing. Then the solution steps we have taken include: 1) Forming a business group that can improve the welfare of the Durian village community with the target groups we are targeting is Durian Village mothers who have a lot of free time; 2) Sharing the tasks of Durian village mothers who took part in the training, so some mothers focused on making crafts and some were given additional assignments to learn more about online marketing; 3) Establish cooperation with parties who are experienced in developing a creative economy based on handicrafts to assist in the training process and in developing the business later. Output targets for the activity include: 1) Establishment of a permanent and continuous coconut leaf craftsman group in Durian village to be able to carry out other activities related to handicrafts; 2) Progress and Final Report; 3) Scientific articles which contain background, rationale, and general description as well as information about handicraft development in Durian village, Central Lombok, which has been carried out by the EDKERDAPA group. Evaluation results indicate that the process and stages of activities have been carried out as planned